Analisis Tindak Tutur Direktif Dalam Novel Layangan Putus Karya Mommy Asf - Everhard Markiono Solissa; Jumriah Jumriah; Azhariah Rachman; Mas’ud Muhammadiah; Andi Saadillah; Yuniar Sakinah Waliulu (Journal on Education, 2023)
This study has two objectives, namely: 1) to describe the form of directive speech acts in novel broken kite by Mommy; 2) to describe the function of directive speech acts in the novel broken kite by Mommy ASF. This type of research is qualitative research. Qualitative research is research with a study method or research method on a problem. The data source for this research uses primary and secondary data. The primary data source in this study is the novel broken kite by Mommy ASF and the secondary data source in this study is in the form of reference book articles related to research problems. data collection used in research is the basic techniques of listening, recapitulation, data transcription, and note-taking techniques. The results of the study found 7 directive speech acts in the novel broken kite by Mommy ASF a: asking, inviting, advising, ordering, begging, forbidding, suggesting, and giving permission. The functions of directive speech acts in the novel broken kite by Mommy ASF are: asking, inviting, advising, ordering, begging, suggesting, giving permission.